Деякі аспекти збереження рідкісних і зникаючих рослин на урбанізованих територіях - Sholl, G.N. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
Separate aspects of conservation of rare and vanishing species of urbanoflora in Krivyi Rih are considered. Some results of successful introduction of the species entered in the Red Book of Ukraine and the World Red List are shown.